Performance Prediction of Bow-Foil Thrusters in Waves Using Unsteady Vortex Element Method - Ioannis Papakalodoukas; Kostas Belibassakis (Journal of Marine Science and Engineering)
In this study, an unsteady vortex element method is applied to the analysis of a horizontal wing in order to investigate its propulsive performance when operating as a biomimetic thruster. The foil undergoes a combined heaving and pitching motion at the same frequency, in a uniform inflow condition, due to its advance at a constant speed. The numerical results are presented and compared to experimental measurements for the propulsion thrust coefficient and the efficiency of the system over a range of motion parameters. The results indicate the significance of 3D effects and show that the present technique can serve for the design of this kind of propulsive system with optimized performance. In the next stage, the wing is examined in a horizontal T-foil arrangement at the bow of a ship as an efficient propulsion system, and its performance in irregular head waves, characterized by a frequency spectrum, is also studied using experiments in a towing tank. In the test cases, a 30% damping of the ship responses in waves is observed with a simultaneous decrease in the total resistance by 5%. The numerical results are compared with data obtained from tank experiments, revealing good agreement, demonstrating the applicability of the present method to the preliminary design of this system for the augmentation of ship propulsion in waves.